2020
DOI: 10.3390/jcm9041087
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Analgesia (MMA) Versus Patient-Controlled Analgesia (PCA) for One or Two-Level Posterior Lumbar Fusion Surgery

Abstract: A multimodal analgesic method was known to avoid the high-dose requirements and dose-dependent adverse events of opioids, and to achieve synergistic effects. The purpose of this study was to compare the efficacy of our multimodal analgesia (MMA) regimen with that of the patient-controlled analgesia (PCA) method for acute postoperative pain management. Patients who underwent one or two-level posterior lumbar fusion (PLF) followed by either MMA or PCA administration at our hospital were compared for pain score, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Our PMPM protocol improved pain control on postoperative day 3, which was consistent with previous studies. Rajpal et al [19] reported that preventative multimodal analgesia improved pain control on all four postoperative days in patients undergoing lumbar fusion surgery, and Choi et al [9] found that multimodal analgesia reduced additional opioid use on postoperative day 2 without increasing pain levels in patients with one-or two-level posterior lumbar fusion surgery compared to a PCA group. In our study, more physical activity might contribute to the slightly increased VAS score and additional opioids' prescription on POD3 in the PMPM group; the analgesic pump would be turned off on POD3, which might contribute to a significantly increased VAS score in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our PMPM protocol improved pain control on postoperative day 3, which was consistent with previous studies. Rajpal et al [19] reported that preventative multimodal analgesia improved pain control on all four postoperative days in patients undergoing lumbar fusion surgery, and Choi et al [9] found that multimodal analgesia reduced additional opioid use on postoperative day 2 without increasing pain levels in patients with one-or two-level posterior lumbar fusion surgery compared to a PCA group. In our study, more physical activity might contribute to the slightly increased VAS score and additional opioids' prescription on POD3 in the PMPM group; the analgesic pump would be turned off on POD3, which might contribute to a significantly increased VAS score in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Poor pain control is associated with patients' dissatisfaction [6], postoperative complications [7], and excessive opioid consumption [8]. Patient-controlled analgesia (PCA) and perioperative multimodal pain management (PMPM) (also known as multimodal analgesia) relive unnecessary suffering after fusion surgery [9]. PCA is a conventional method that allows the patients to self-administer intravenous opioid medication to control pain [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several risk factors for high postoperative pain scores have been established [6,7]. Nearly all types of surgery that yield high postoperative pain can be treated with IV-PCA in the acute phase; examples of such surgeries include spine and other complex orthopedic surgeries, such as knee and hip [15], open abdominal [16] and non-ambulatory laparoscopic surgery [17]; and thoracic [18], major cervicofacial and reconstruction surgeries [19], including breast surgeries [20]. In addition to initial severe postoperative pain, some surgeries can also yield chronic postoperative pain such as cardiac [21], knee [22] shoulder [23] and hip pain [24].…”
Section: Indications and Benefits Of Pcamentioning
confidence: 99%
“…Opioid use has been associated with severe adverse effects, including respiratory depression, postoperative pruritus, urinary retention, gastrointestinal events, sedation, and allergic reactions [9]. Combining nonsteroidal anti-inflammatory drugs (NSAIDs) with opioids may also reduce adverse effects and the required opioid dose [10][11][12][13]. The ASA Task Force on Acute Pain Management reports that opioids in combination with NSAIDs, COXIBs, or acetaminophen may be superior to opioid use alone [5].…”
Section: Introductionmentioning
confidence: 99%